2018
DOI: 10.18203/2394-6040.ijcmph20181691
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of risk of infections to health care professionals and its preventive practices among medical students: a cross-sectional study

Abstract: Background: Occupational health is a neglected public health issue among healthcare workers in developing countries leading to health care associated infections both to patients and medical students unless infection prevention and control (IPC) measures followed. This study was conducted with an aim to assess the degree of knowledge regarding infection in health care professionals and infection control measures among medical students.Methods: A cross-sectional study was conducted from June 1 to July 31, 2017 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Savanthe AM et al 10 observed that knowledge of the medical students regarding infection source is adequate but infection prevention practices was relatively less particularly needle stick injury prevention, hand hygiene techniques, blood borne infection control. Hospitals should reinforce the knowledge of universal precaution continually and recommended performing infection control education programs at the college level before starting the clinical practice years along with seminars and feedback, highlighting importance of IPC guidelines to increase safety of our graduates and patients.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Savanthe AM et al 10 observed that knowledge of the medical students regarding infection source is adequate but infection prevention practices was relatively less particularly needle stick injury prevention, hand hygiene techniques, blood borne infection control. Hospitals should reinforce the knowledge of universal precaution continually and recommended performing infection control education programs at the college level before starting the clinical practice years along with seminars and feedback, highlighting importance of IPC guidelines to increase safety of our graduates and patients.…”
Section: Review Of Literaturementioning
confidence: 99%